2015
DOI: 10.1371/journal.pone.0133609
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Potentials and Memory/Cognition Tests Validate Brain Atrophy as Measured by 3T MRI (NeuroQuant) in Cognitively Impaired Patients

Abstract: To our knowledge, this is the largest study evaluating relationships between 3T Magnetic Resonance Imaging (MRI) and P300 and memory/cognitive tests in the literature. The 3T MRI using NeuroQuant has an increased resolution 15 times that of 1.5T MRI. Utilizing NeuroQuant 3T MRI as a diagnostic tool in primary care, subjects (N=169; 19–90 years) displayed increased areas of anatomical atrophy: 34.62% hippocampal atrophy (N=54), 57.14% central atrophy (N=88), and 44.52% temporal atrophy (N=69). A majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Moreover, it was found that there were significant direct correlations between hippocampal volumes and performance on several different neuropsychological tests when patients and healthy subjects were combined. These findings are in agreement with that found for non-African American populations in Braverman et al [41] who used 3T MRI with sophisticated NeuroQuant® software to measure both evoked potentials and memory/cognition in a mixed gender and age group of cognitively impaired patients. The study revealed hippocampal, central and temporal lobe atrophy, with delayed latency of evoked potentials marginally associated with temporal lobe atrophy.…”
Section: Observations and Discussionsupporting
confidence: 92%
“…Moreover, it was found that there were significant direct correlations between hippocampal volumes and performance on several different neuropsychological tests when patients and healthy subjects were combined. These findings are in agreement with that found for non-African American populations in Braverman et al [41] who used 3T MRI with sophisticated NeuroQuant® software to measure both evoked potentials and memory/cognition in a mixed gender and age group of cognitively impaired patients. The study revealed hippocampal, central and temporal lobe atrophy, with delayed latency of evoked potentials marginally associated with temporal lobe atrophy.…”
Section: Observations and Discussionsupporting
confidence: 92%
“…26 EEG as a functional aspect, the early correlation changes of cognition had been raised by the previous studies. 9,27,28 For example, alpha and delta powers were found to be manifestations of cognitive decline, including MCI and dementia. Cognitive estimation is an objective way of evaluating cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal lobe atrophy was correlated with delayed P300 in a group of cognitive dysfunction and brain atrophy group. 9 The spectrum-specific analysis and standardized low-resolution brain electromagnetic tomography (sLORETA) connectivity construction could screen the key modules of dementias. EEG-based sLORETA analysis showed that Alpha-1 relative power current density in parietooccipital brain areas, Beta-1 in the frontal lobe, and delta relative power current density were found to be altered in vascular cognitive impairment, no dementia (VCIND) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies elucidate the links between memory and cognitive impairments and negative changes observed in P300 latency and amplitude (Ozen et al, 2013). Because of this evidence, the P300 serves as a sensitive marker for cognitive dysfunction that affects neurological, psychiatric, and developmental areas of the human body (Braverman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%